Effective Strategies for Internalizing Islamic Religious Education Values in the Character Development of Students in Secondary Schools - Miftahul Aeni (PT. Nawa Edukasi Nusantara, 2025)
Islamic Religious Education (PAI) has a central role in shaping the character of students based on Islamic moral and spiritual values. This study aims to examine the strategy of internalizing PAI values in the process of forming students' character through a qualitative approach with the literature study method. Data was obtained from various literature such as books, scientific journals, and relevant previous research results. The results of the study show that the process of internalizing PAI values consists of three main stages: value transformation, value transactions, and value transinternalization. Each stage emphasizes cognitive, affective, and psychomotor aspects in value learning. The success of internalization depends heavily on the example of teachers, a supportive school environment, and interactive and reflective learning methods. In addition, several supporting and inhibiting factors were also found, such as the role of family, media, and school culture. With the right strategy, the internalization of PAI values can be a strong foundation in shaping students' character in a complete and sustainable manner.